2009
DOI: 10.1021/es9010114
|View full text |Cite
|
Sign up to set email alerts
|

Not All Salmon Are Created Equal: Life Cycle Assessment (LCA) of Global Salmon Farming Systems

Abstract: We present a global-scale life cycle assessment of a major food commodity, farmed salmon. Specifically, we report the cumulative energy use, biotic resource use, and greenhouse gas, acidifying, and eutrophying emissions associated with producing farmed salmon in Norway, the UK, British Columbia (Canada), and Chile, as well as a production-weighted global average. We found marked differences in the nature and quantity of material/energy resource use and associated emissions per unit production across regions. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
220
2
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 248 publications
(236 citation statements)
references
References 26 publications
12
220
2
2
Order By: Relevance
“…In some cases, extant systems may be preferable. Well-managed fisheries and aquaculture might similarly stand to displace a share of terrestrial animal protein production, also with careful attention to tradeoffs (37). Across the board reductions in per capita consumption of livestock products should similarly be a policy priority.…”
Section: Resultsmentioning
confidence: 99%
“…In some cases, extant systems may be preferable. Well-managed fisheries and aquaculture might similarly stand to displace a share of terrestrial animal protein production, also with careful attention to tradeoffs (37). Across the board reductions in per capita consumption of livestock products should similarly be a policy priority.…”
Section: Resultsmentioning
confidence: 99%
“…Such temporal data are lacking for Scotland, but similar reduc tions are likely to have occurred. However, the seawater FCR in Scotland (1.3) has been suggested to be higher than in Norway (Pelletier et al, 2009). …”
Section: Reducing Wastementioning
confidence: 96%
“…Recent (snapshot) Life Cycle Assess ments indicate that the global environmental pressures of farmed salmon products -via resource use (energy) and emissions (green house gases, nitrogen phosphorous) -are similar to those from fishery production, and lower than terrestrial meat farming (Ellingsen and Aanondsen, 2006;Pelletier and Tyedmers, 2007;Hall et al, 2011;Ytrestøyl et al, 2011). Nevertheless, salmon pro duction in Scotland is judged to have higher impacts than in other countries due to differences in feed ingredients (Pelletier et al, 2009). …”
Section: Reducing Resource Inputs and Environmental Pressuresmentioning
confidence: 99%
“…Much of the contribution comes from the use of vegetable based ingredients within the diet, especially proteins, despite there being around 48% fish ingredients. This is because some of the plant proteins, such as types of gluten, are extremely energy intensive in their processing (Pelletier et al 2009). The individual ingredients cannot be discussed because of confidentiality.…”
Section: Lcia Of Scottish Salmon Grow-out Feedsmentioning
confidence: 99%
“…Pelletier et al (2009) also showed that some vegetable ingredients were energy intensive and Papatryphon et al (2004) showed that salmonid feeds containing large quantities of vegetable ingredients had higher impacts than those with high levels of fish ingredients. However, it should be noted that these studies used different methodology in some cases and would have had different inputs to the data presented here.…”
Section: Lcia Of Scottish Salmon Grow-out Feedsmentioning
confidence: 99%